Evaluation of Nanosize NbC Precipitates in HSLA Steel through Microstructural Analysis and Small Angle Neutron Scattering - Okuda, Kaneharu; Yamada, Katsumi; Ishida, Toshinori; Nakamichi, Haruo; Ohnuma, Masato (Materials Science Forum, 2018)
Nano size precipitate morphologies are very important for considering the precipitate hardening mechanism of HSLA steels. Systematic analysis of precipitates from nano scale to bulk scale were carried out using Nb bearing hot rolled steels through transmission electron microscopy (TEM) observations and chemical analysis of precipitates by solvent extraction. A small angle neutron scattering (SANS) experiment was also performed using a Hokkaido Univ. compact neutron source to understand average precipitate size. Results show that both changes in hardness and the amount of precipitates (under 20nm in size) have the same tendency. Precipitate is recognized as NbC plates, which have coherency with the steel matrix by Baker-Nutting orientation relationships. A row of precipitates, formed on the interface between austenite and ferrite during transformation, is also apparent. The SANS profile shows that small size precipitate formation is detected even though the amount of precipitation is small. In addition, the magnetic scattering component of the SANS profile has high sensitivity to NbC precipitates compared with that of the nucleus scattering component. By comparing precipitate data from comprehensive experiments, we consider the relationship between precipitate behavior and the hardening mechanism.